Fibrous Obliteration in a Middle-Aged Woman: A Case Report - Zarghami, Anita; Ebrahimi, Mahsa; Tajik, Alireza; Ahmadi, Samaneh (Novelty in Biomedicine, 2024)
Background: Fibrous obliteration or appendiceal neuroma is a rare type of appendiceal tumor that causes appendiceal obstruction and then presents as appendicitis. This neural tumor has no specific presentation and, after appendectomy, is diagnosed by the pathologist accidentally. Fibrous obliteration is described as a proliferative lesion. The pathogenesis of this lesion is unknown, but it is mentioned that the etiology of this problem is secondary to recurrent inflammation processes. These processes cause neuroendocrine cell hyperplasia in the submucosa and lamina propria of the wall of the appendix. The repetitive occurrence of these sub-clinical inflammatory processes causes fibrosis. Cases Report: We presented a 55-year-old woman who was referred to our clinic with persistent pain in the right lower quadrant for five days in this report. The pain mimicked appendicitis presentation, and it suddenly started from the periumbilical area and then shifted to the right lower quadrant of the abdomen. Her laboratory study showed a 9600/microliter white blood cell count with 70% neutrophils. An increase in the appendix loop with 9 millimeters diameter was reported in the ultrasound. There was also severe fat haziness around the tissues and visceral inflammation of the terminal ileum in the sonogram. She underwent an appendectomy after the diagnosis of appendicitis, and the pathologist diagnosed fibrous obliteration or appendiceal neuroma. Conclusion: It is concluded that fibrous obliteration or appendiceal neuroma mimics acute appendicitis, and in patients with this presentation, appendectomy is the best choice for treatment. The main diagnostic method is pathologic assessment, and it is important for the differentiation of this tumor from other malignant tumors of the appendix because fibrous obliteration is a benign tumor.